REAKSI PASAR MODALTERHADAP PERISTIWA PELANTIKAN KABINET INDONESIA MAJU HASIL RESHUFFLE JILID I TAHUN 2020 - Tenaya, Ida Bagus Jelantik; Ramantha, I Wayan (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2022)
This research was conducted on the Indonesia Stock Exchange on LQ45 indexed stocks. The dependent variable in this study is the market reaction which is measured by abnormal returns around the date of the inauguration of the Indonesia Maju cabinet as a result of the reshuffle volume I in 2020. The number of samples taken is 43 companies, using purposive sampling technique. Data collection was carried out by archival research methods. Based on the results of the analysis, it was found that there was a significant difference in abnormal returns before and after the inauguration of the Indonesia Maju cabinet as a result of the 2020 reshuffle volume against the LQ45 indexed company shares listed on the IDX. This happened because the inauguration of the Indonesia Maju cabinet resulting from the 2020 reshuffle volume I contained information so that the market needed fast time to achieve a new balance. Investors in this study react quickly in absorbing information so that it is in accordance with the semi-strong form of efficient market.